Volumetric and acetabular changes in the bony pelvis associated with primary closure of classic bladder exstrophy. Issue 6 (December 2020) - Manyevitch, Roni; Dunn, Emily; Zaman, Mohammad H.; Maruf, Mahir N.; Benz, Karl; Clennon, Emily K.; Wu, Wayland J.; Davis, Rachel; Di Carlo, Heather N.; Sponseller, Paul D.; Stec, Andrew A.; Gearhart, John P.
Summary: Introduction: Repair of classic bladder exstrophy (CBE) is known to alter dimensions of the bony pelvic ring. Pelvic volume and acetabular configuration are additional metrics which merit analysis in the reconstruction process. Advances in magnetic resonance imaging (MRI) allow for precise elucidation of such anatomy in pediatric patients, providing enhanced knowledge of how primary reconstruction may impact factors in pelvic health. Methods: An IRB-approved exstrophy-epispadias database of 1337 patients was reviewed for patients with CBE who had pelvic MRI performed before and after repair. Pelvic MRIs were analyzed by a pediatric radiologist, and three-dimensional volumetric renderings of the true pelvis were calculated. Pre- and post-closure imaging were compared, in addition to imaging from age-matched controls without pelvic pathology. Cartilaginous acetabular index and version angles were also calculated and compared between groups. Results: Eighteen patients with post-closure imaging, 14 of whom also had pre-closure imaging, and 23 control patients (ages 0–365 days) were included. The median ages at pre- and post-closure scan were 2 and 178 days, respectively. Osteotomy was performed in 6 (33%) of the closures. The median segmented pelvic volumes were 89 cm 3 in the pre-closure group, 105 cm 3 in the post-closure group, and 72 cm 3 in the control group. At a given age, patients with CBE pre-closure had the largest pelvic volume, and those without bladder exstrophy demonstrated the smallest pelvic volumes (Summary Figure ). CBE patients' pelvic volumes were overall lower following repair, relative to age ( p  = 0.007). Cartilaginous acetabular version angle increased following closure, with acetabular orientation converting from retroversion to anteversion in all cases. However, only acetabular version angles were significantly different between groups. Discussion: This study found that pelvic volume significantly decreased relative to age following primary repair of CBE, but that it did not correct to control levels. Similarly, acetabular retroversion that is naturally seen in exstrophy patients was converted to anteversion post-closure but did not become completely normal. Knowledge of these persistent anatomical anomalies may be useful in treatment of future concerns related to exstrophy, such as continence achievement, pelvic organ prolapse, and potential gait disturbances. Lack of significant differences between study groups regarding acetabular index angles can give assurance to providers that hip dysplasia is neither a natural concern nor iatrogenically inflicted through reconstruction. Conclusions: The primary closure of exstrophy results in pelvic volumes and anteverted acetabula that more closely resemble those without bladder exstrophy, compared to pre-closure findings. Summary Figure Demonstrates the change in pelvic volume by the age of the patients in the pre-closure, post-closure, and control groups. (Abbreviations: CBE, classic bladder exstrophy). Summary Figure